The Short-Term Value of the “Healthy Primary School of the Future” Initiative: A Social Return on Investment Analysis - Oosterhoff, Marije; van Schayck, Onno C. P.; Bartelink, Nina H. M.; Bosma, Hans; Willeboordse, Maartje; Winkens, Bjorn; Joore, Manuela A. (Frontiers in Public Health, 2020)
Background: This study examines the social return on investment (SROI) of the ‘Healthy Primary School of the Future’ initiative after 2 years. Methods: Healthy Primary Schools of the Future (HPSF) provide a healthy lunch and daily structured physical activity sessions, whereas Physical Activity Schools (PAS) focus on physical activity only. We evaluated the 2-year investments and effects (N=1676 children) of both school environments (4 schools) compared to control schools (4 schools). Investments and outcomes were grouped within the healthcare, education, household & leisure, and labour & social security sector. Outcomes that could be expressed in monetary terms were used for the calculation of social return on investment. Results: HPSF and PAS created outcomes for the healthcare sector by favorable changes in health behaviors, body mass index [both significant], and medical resource use [not significant]). Outcomes for the education sector included a favorable impact on perceived social behaviors and school satisfaction, and absenteeism from school [latter not significant]), and more engagement with the community was experienced. The per child investments, €859 (HPSF) and €1017 (PAS), generated a benefit of €8 (HPSF) and €49 (PAS) due to reduced school absenteeism and medical resource use. Conclusions: Within two years of intervention implementation, the HPSF initiative created outcomes in several sectors, but the benefits did not outweigh the investments. Follow-up assessments as well as modeling long-term outcomes are needed to assess the total value of the interventions. Until then, the SROI framework can inform strategies for obtaining stakeholder support and intervention implementation.